(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2013)
This paper briefly discusses the main activities carried out by University of Padua at the archaeological site of Nora since 1990. Most effort has been addressed to the excavation, publication and enhancement of two important historical complexes located near the western slopes of the peninsula: the Forum, along with the underlying pre-Roman district, and the near “Roman Temple”. Fieldwork has also allowed comparing several multi-stratified sequences which have made it possible to understand the evolution of a wide urban area from the Phoenician Age to Late Antiquity. Another field of research has been the relationship between the ancient communities living at Nora and environmental resources. This research area has been pursued through a number of thematic and spatial investigations, such as the census of urban cisterns, the survey of stone quarries at Is Fradis Minoris, the study of the ancient coast line, a functional analysis of the areas by the shore, the study of previous underwater investigations and the development of evaluation tools to gauge the archaeological risk along the coast line.